2007
DOI: 10.1016/j.jcrs.2007.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Rotational stability of a single-piece hydrophobic acrylic intraocular lens: New method for high-precision rotation control

Abstract: Using a suitable measuring method that takes into account the cyclorotation of the eye, it was possible to precisely determine IOL rotation using picture pairs taken in chronological sequence. The IOL design examined in the study is recommended as a toric IOL because of its good rotational stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 12 publications
(8 reference statements)
3
62
0
2
Order By: Relevance
“…Weinand and colleagues used this technique immediately and 6 months after IOL implanation in 17 of 40 eyes implanted with the AcrySof SA60AT. 10 The other images could not be analysed due to insufficient dilation (IOL orientation required visibility of both haptic-optic junctions) and poor image quality. In addition, a different camera was used on each occasion and repeatability of analysis and image capture was not assessed.…”
mentioning
confidence: 99%
“…Weinand and colleagues used this technique immediately and 6 months after IOL implanation in 17 of 40 eyes implanted with the AcrySof SA60AT. 10 The other images could not be analysed due to insufficient dilation (IOL orientation required visibility of both haptic-optic junctions) and poor image quality. In addition, a different camera was used on each occasion and repeatability of analysis and image capture was not assessed.…”
mentioning
confidence: 99%
“…[19] The most important factor is the position of multifocal-toric IOL during surgery and its rotation after surgery. [20] In the present study, we evaluated open-loop-haptic AcrySof IQ restore multifocal toric IOL (Alcon) and plate-haptic Acriva reviol multifocal toric IOL (VSY) lenses in terms of postoperative rotational stability, residual astigmatism and uncorrected distance and near visual acuity. We found that rotational degree of plate haptic IOL was higher in the postoperative 1st and 3rd months, although it is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The technique with a pen and a pendulum marker at 0p and 180p was used and demonstrated to be imprecise, moreover, during the surgery it is not uncommon to lose the precise axis due to the ink washout by balance salt solution (BSS). Although, many techniques have been developed to determine the postoperative IOL rotational stability, new studies should be worried in precisely mark the axis prior surgery, such as the computer model based on preoperative slitlamp examination demonstrated by Robert Osher,MD on the American Society of Cataract Refractive Surgery meeting-San Francisco-2009 called "Fingerprinting technique" (7,8) .…”
Section: Discussionmentioning
confidence: 99%